Frontier Justice, Colonial Justice, and the Spaces in Between in the Southern Philippines, 1898-1913 - Hawkins, Michael C. (Silliman Journal, 2022)
This research note explores the meanings and function of frontier violence in the southern Philippines during a period of American military rule (1898-1913). It looks specifically at notions of colonial and frontier justice as demonstrated in the local press, and links these to the larger ideals and objectives of American colonialism on a distant periphery.